USE OF GRAPHIC NOVELS IN LANGUAGE EDUCATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Graphic novels have emerged as an effective pedagogical tool in language education, combining visual literacy with linguistic skills to enhance learners’ comprehension and engagement. This article is to consider the use of graphic novels in language teaching, emphasizing their potential to support vocabulary acquisition, reading comprehension, and intercultural competence. Drawing on existing literature and case studies, the article highlights how graphic novels offer a multimodal learning experience that provides with diverse learning styles and fosters critical thinking.